Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1002/adem.200700224
|View full text |Cite
|
Sign up to set email alerts
|

Surface Topography, Surface Energy and Wettability of Magnetron‐Sputtered Amorphous Carbon (a‐C) Films and Their Relevance for Platelet Adhesion

Abstract: Diamond-like carbon (DLC) and amorphous carbon (a-C, a-C:H) coatings, respectively, have been proposed since many years as potential materials for biomedical applications due to their chemical inertness, low friction coefficient, high wear resistance, bio-and haemocompatibility. [1][2][3][4][5][6] The feasibility of amorphous carbon coatings was investigated for a variety of applications like surgical needles, [2] orthopaedic implants and prostheses, [7][8][9][10][11] medical guidewires, [12][13][14][15] coron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 79 publications
(88 reference statements)
3
21
0
1
Order By: Relevance
“…Interestingly, the correlation between the patterns in platelet adhesion and spreading in the sequence Ce-CeWb-CeWbHt surfaces with the behavior of the polar energy agrees with the results of the study of amorphous carbon films [40] where platelet activation gradually decreased with γ p .…”
Section: Biological Implicationssupporting
confidence: 80%
“…Interestingly, the correlation between the patterns in platelet adhesion and spreading in the sequence Ce-CeWb-CeWbHt surfaces with the behavior of the polar energy agrees with the results of the study of amorphous carbon films [40] where platelet activation gradually decreased with γ p .…”
Section: Biological Implicationssupporting
confidence: 80%
“…With the change in deposition pressure, target current and substrate bias voltage, there was a change in the surface roughness and an associated variation in the water contact angle and surface energy as shown in Fig. 8a, b and c. A similar finding was reported by Stüber et al who observed a linear change in the surface energy of the sputtered coatings with increasing surface roughness [36]. From this study it was concluded that of the deposition parameters investigated the deposition pressure had the most significant influence on enhancing both surface roughness and energy of the NiO x coatings.…”
Section: Surface Energy Measurementssupporting
confidence: 72%
“…Due to these attributes, DLC films are widely used for surface protection in cutting tools [2;3], magnetic storage discs [4], biomedical devices [5][6], antireflection coatings, and optical sensors [7]. Various mechanisms have been proposed in order to describe the formation of sp 3 bonds in DLC films [1,[8][9][10][11]; among them, the most accepted view for amorphous carbon films without significant hydrogen incorporation is that the sp 3 formation is triggered by subsurface densification generated by subplantation of energetic deposited species [1,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%